2012
DOI: 10.1063/1.3674275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electric fields on the depolarization temperature of Mn-doped (1-x)Bi1/2Na1/2TiO3-xBaTiO3

Abstract: Articles you may be interested inElectric-field-temperature phase diagram of the ferroelectric relaxor system (1−x)Bi1/2Na1/2TiO3−xBaTiO3 doped with manganese J. Appl. Phys. 115, 194104 (2014) . Temperature-dependent permittivity e 0 (T) and thermally stimulated depolarization currents (TSDC) of poled samples were measured under identical heating conditions to clarify the depolarization mechanism. In both methods, the influence of electric bias fields on the transition temperature was investigated. Fields appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
107
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 43 publications
17
107
0
4
Order By: Relevance
“…However, there are other definitions of T d such as the steep reduction of remnant polarization [7], or the phase transition temperature from ferroelectric (FE) to anti-ferroelectric (AFE) or to relaxor anti-ferroelectric or to relaxor [8,[22][23][24][25]. In this study, T d was identified from the measurement of the dielectric loss (tand) versus temperature.…”
Section: Effects Of Extra Barium On Depolarization Temperaturementioning
confidence: 99%
“…However, there are other definitions of T d such as the steep reduction of remnant polarization [7], or the phase transition temperature from ferroelectric (FE) to anti-ferroelectric (AFE) or to relaxor anti-ferroelectric or to relaxor [8,[22][23][24][25]. In this study, T d was identified from the measurement of the dielectric loss (tand) versus temperature.…”
Section: Effects Of Extra Barium On Depolarization Temperaturementioning
confidence: 99%
“…47 This was ascertained using further field dependence together with temperature dependence of permittivity and depolarization current. 48 Here, we are fundamentally interested in ferroelectric-relaxor transitions and determine the peak in tand in order to quantify the ferroelectric-relaxor transition (T F-R ). 31,48 This temperature decreases with increasing Zn 2þ -content from 55 C in 2BZT to 45 C in 3BZT.…”
Section: B Measurements At Elevated Temperaturesmentioning
confidence: 99%
“…48 Here, we are fundamentally interested in ferroelectric-relaxor transitions and determine the peak in tand in order to quantify the ferroelectric-relaxor transition (T F-R ). 31,48 This temperature decreases with increasing Zn 2þ -content from 55 C in 2BZT to 45 C in 3BZT. Eventually, no transition is observed for 4BZT above 25 C. The general trend suggests that the ferroelectric-relaxor transition lies below room temperature.…”
Section: B Measurements At Elevated Temperaturesmentioning
confidence: 99%
“…2 Furthermore, recent investigations of Na 1/2 Bi 1/2 TiO 3 -xat.%BaTiO 3 (NBT-x%BT) have revealed giant strain and longitudinal piezoelectric constants as high as d 33 ¼ 500 pC/N for compositions near a morphotropic phase boundary (MPB) around x ¼ 5.5-6.5. [3][4][5][6][7][8][9][10][11][12][13] In spite of a non-rhombohedral average structure model for NBT at room temperature was supported by highresolution single-crystal x ray diffraction, 14 it is still widely accepted that NBT undergoes a phase transformational sequence of paraelectric cubic (C) ! paraelectric tetragonal (T) !…”
mentioning
confidence: 99%